The Marketing Strategy of Waste-Processed Craft Product in Pontianak City - Gusti Tedi Daryanto; Dewi Kurniati; Shenny Oktoriana (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
Pontianak city produced 400 tons of waste every day. The prevention of waste had been done in various ways; one of them was the utilization of waste by 8 waste banks to be used as craft products with an economic value. The aim of the research was to formulate alternative priority marketing strategies for processed waste craft products in Pontianak. The research method that used was descriptive qualitative methods, surveys and interviews with key informants to obtain SWOT criteria and alternative strategies. This research used primary and secondary data, primary data obtained from interviews and surveys that included waste banks data and respondent data, secondary data included waste production in Pontianak City, waste banks in Pontianak City. The data analysis used the combination of Analytical Hierarchy Process (AHP) and Strength Weakness Opportunities Threats (SWOT). The research results showed that the alternative priority for the marketing strategy of processed waste products was the strategy to improve Human Resources (0.462), such as product innovation, conducted comparative study with UKM (small-medium enterprises), made observations of products that people were interest in; information and technology improvement strategies (0.403), such as recruited and trained employees to understand information technology; institutional improvement strategies (0.135), such as upgraded and focused group discussions in the Waste Bank Forum, managed the requirements for marketing in supermarkets